Is the production of embryos in small-cale farming an economically feasible enterprise? - Romero-Zúñiga, Juan José (2015)
The present assay attempts to evaluate the feasibility of using embryo transfer in small community farmers by in vivo study and by modelling the results obtained. From the total of 59 donor cows, 62.7% responded to treatment, with a significant difference (p = 0.002) in the percentage of the response between breeds, being 90.5% (19/21) in Holstein and 47.4% (18/38) in Brahman. A total of 283 embryos were graded as transferable, while 141 as non-transferable, without difference in the percentage of transferable embryo by breed (p = 0.18). The mean of transferable embryos graded as class I and II was not different between Holstein and Brahman (p = 0.96 and p = 0.92, respectively); besides, no differences were observed in the other grades (non-transferable). The highest difference in costs, regardless of its quality by breed, was seen in the lower levels of probable fertility of the embryo transferred, even reaching several hundred dollars. When modelling the expected costs for embryo produced and transferred, values can reach nearly $2000.00 when the probable fertility is only 10%. However, when the probable fertility was 60%, embryo cost was close to $300.00. This technology seems to be viable on average or high-scale systems, having a superovulatory response between 60 and 80% with 4-6 transferrable embryos. Yet, in small-scale farming, due to the reduced number of donors and/or recipients, the costs surpass the economical feasibility of the technique. © 2015 Blackwell Verlag GmbH.